MODEL PENENTUAN LINI RAKIT SUMBER SERENTAK DENGAN KETERSEDIAAN ALTERNATIF SUMBER - Filas Tanjung, Harfes
Abstract:. One of the main problems in designing assembly work is line balancing. Buckhin and Tzur (2000) and Buckhin and Rubinovitz (2003) discussed the assembly line problem with equipment selection. Both pieces of research assumed that flexible equipment is needed on the assembly line to perform different operations and has alternative equipment with different process capability. Flexible resources such as operator, machine, equipment, jig, and fixture are required on the workstation simultaneously. This research discusses a model of designing an assembly line requiring simultaneous resources available in the line with alternatives. The objective of the proposed model is to minimize resource acquisition cost, subject to several constraints concerning precedence diagram, operation time, cycle time, line balancing, workstation, values of decision variables, and elaborate problem (zoning constraints and must-do task). This model has been verified by using hypothetical data to shows behavior of the solution for the model. The research also shows that cycle time influences resource cost and s parameter influences the number of parallel workstations.